2012
DOI: 10.1002/adma.201200157
|View full text |Cite
|
Sign up to set email alerts
|

Random Composites of Nickel Networks Supported by Porous Alumina Toward Double Negative Materials

Abstract: Random composites with nickel networks hosted randomly in porous alumina are proposed to realize double negative materials. The random composite for DNMs (RC-DNMs) can be prepared by typical processing of material, which makes it possible to explore new DNMs and potential applications, and to feasibly tune their electromagnetic parameters by controlling their composition and microstructure. Hopefully, various new RC-DNMs with improved performance will be proposed in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
145
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 264 publications
(163 citation statements)
references
References 25 publications
4
145
1
Order By: Relevance
“…In those porous metal/ceramic composites, metal particles dispersed on the pore walls of porous ceramic, leading to the ultralow percolation threshold, hence the suppressed leakage conductance loss and eddy current loss. 10,11,32 Similarly, Ameli et al 33 prepared a class of porous polymer nanocomposites consisting of multi-walled carbon nanotubes (MWCNT) dispersed on the pore walls of porous polymer. And it is shown that the porous MWCNT/polymer composites exhibit signicantly high permittivity, ultralow percolation threshold and low dielectric loss.…”
Section: -31mentioning
confidence: 99%
See 3 more Smart Citations
“…In those porous metal/ceramic composites, metal particles dispersed on the pore walls of porous ceramic, leading to the ultralow percolation threshold, hence the suppressed leakage conductance loss and eddy current loss. 10,11,32 Similarly, Ameli et al 33 prepared a class of porous polymer nanocomposites consisting of multi-walled carbon nanotubes (MWCNT) dispersed on the pore walls of porous polymer. And it is shown that the porous MWCNT/polymer composites exhibit signicantly high permittivity, ultralow percolation threshold and low dielectric loss.…”
Section: -31mentioning
confidence: 99%
“…However, the interfacial polarization will gradually lag behind the external electric eld with increasing frequency, leading to the decrease of 3 0 . However, when the nickel content is near or above the percolation threshold, the composites dielectric spectra will follow the Drude model, 10,11,41,42 leading to the anomalous frequency dispersion of permittivity (Fig. 4a).…”
Section: 42mentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, carbothermic reduction has become a promising synthesis route for high temperature ceramics because of its low requirements on starting materials. Both industrial raw materials such as commercial alumina and quartz and natural minerals such as sintered bauxite and kaolin can be adopted as starting materials, leading to great industrialization potential [19,20,[22][23][24][25]. Some attempts have been done to synthesize highly pure Al 4 SiC 4 by carbothermic reduction [17].…”
Section: Introductionmentioning
confidence: 99%